Blow up of solution for the generalized Boussinesq equation with damping term - Polat, Necat; Kaya, Dogan (Walter de Gruyter Gmbh, 2006)
We consider the blow up of solution to the initial boundary value problem for the generalized Boussinesq equation with damping term. Under some assumptions we prove that the solution with negative initial energy blows up in finite time.
Keywords: damped Boussinesq equation; generalized Boussinesq equation; blow up of solution; initial boundary value problem